Revolutionizing Mushroom processing: Innovative techniques and technologies - Sangeeta; Sharma, Dhriti; Ramniwas, Seema; Mugabi, Robert; Uddin, Jalal; Nayik, Gulzar Ahmad (Food Chemistry: X, 2024)
In recent years, the global mushroom industry has seen remarkable growth due to its nutritional benefits, increasing market value, and rising consumer demand. Mushrooms are valued for their unique flavor, low sugar and salt, and rich Vitamin D content. In India as well as across the globe, mushroom cultivation is becoming increasingly popular among new entrepreneurs, leveraging the diverse agro-climatic conditions and substantial agricultural waste. Various government policies are also fostering research and development in this sector. To extend shelf life and preserve quality, various preservation techniques are employed, including drying, freezing, canning, high-pressure processing and modified atmosphere packaging. Furthermore, cutting-edge technologies such as nuclear magnetic resonance and spectroscopy are improving post-harvest processing, helping to maintain sensory properties and nutritional content. Automation is also transforming mushroom processing by enhancing efficiency and scalability. This review examines the innovative methods and technologies driving advancements in mushroom production and quality worldwide. •Mushroom cultivation offers a profitable agribusiness, enhancing resource use, circular economy, and nutrition.•Mushrooms are increasingly used in soups, meats, and other processed foods, supported by automation.•NMR, imaging, and spectroscopy maintain sensory & nutritional properties of mushroom.•Advanced methods like HPP and MAP enhance mushroom preservation and flavor.